PEMANFAATAN KONSULTAN TEKNIK KONSTRUKSI DAN INSPEKSI TERHADAP FINANSIAL, KOMPLEKSITAS DAN PENJADWALAN PROYEK PEMBANGUNAN JALAN RAYA - Situmorang, Reinold; Mendoza, Dominique (Universitas Negeri Medan, 2024)
The Ministry of Public Works and Housing is responsible for the construction and maintenance of complex transportation networks. However, they face challenges related to their construction staff, including factors such as age, experience level, turnover, retirement, and increasing reliance on consulting services to manage construction operations. To meet the growing needs of the project, utilizes the services of construction inspection and engineering consultants to fulfill the need for construction-related personnel. This research aims to fill this information gap by analyzing a database of 154 completed highway construction projects. The results of the investigation showed that projects that employed consultants exhibited greater levels of full-time equivalent construction staffing compared to projects that relied solely on agency staff. The use of consultants produced no discernible effect on project expenditures compared to programs that relied exclusively on agency personnel. The use of consultants in projects resulted in an average cost overrun of 20.2%, but projects managed by agency staff experienced an average schedule overrun of 27.7%, indicating that on average the projects were completed ahead of schedule. The observed schedule differences showed statistical significance.